Polish Women in Exile to Siberia in the 19th Century – Autobiographical Reflection in Women’s Narratives - Michalska-Bracha, Lidia (Respectus Philologicus, 2018)
[straipsnis ir santrauka anglų kalba]
Keywords: nėra